2015
DOI: 10.1186/s40748-015-0023-4
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of determinants of birth weight of neonates in the Greater Accra region of Ghana

Abstract: BackgroundBirth weight is a major determinant of infant morbidity and mortality. Fetal undernourishment means an increased risk of dying during a baby’s early months and years. Birth weight has emerged as the leading indicator of infant health and welfare and the central focus of infant health policy. The issues have not been comprehensively evaluated in part due to lack of or limited empirical data. To this end, this study is aimed to evaluate the effects of maternal determinants on the birth weights of neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
4
4
1
1
Order By: Relevance
“…We found that male babies were less likely to be born with LBW, which is consistent with some studies [3334]. However, a conflicting finding was reported in Zimbabwe where female babies were less likely to be born with LBW [16].…”
Section: Discussionsupporting
confidence: 91%
“…We found that male babies were less likely to be born with LBW, which is consistent with some studies [3334]. However, a conflicting finding was reported in Zimbabwe where female babies were less likely to be born with LBW [16].…”
Section: Discussionsupporting
confidence: 91%
“…Women's level of education was also not a direct predictor of birth weight. These results are consistent with those of other authors [33,17,44] who found that educational attainment did not have a significant effect on birth weight.…”
Section: It Is Clear Fromsupporting
confidence: 93%
“…The well-being index in this study had no significant influence on baby weight at birth as in the work of Tabrizi and Saraswathi [17] in Iran and Atuahene et al [44] in Ghana. Nevertheless, results contrary to ours have been observed elsewhere [12,13].…”
Section: It Is Clear Fromcontrasting
confidence: 53%
“…Similar findings were reported in previous studies. 31,32 However, a study in Zimbabwe found opposite results showing that female newborns were less likely to be born with LBW. 33 Little is known about the sex differences in the likelihood of being LBW.…”
Section: Discussionmentioning
confidence: 99%